Efektivitas Sistem Kearsipan di Badan Kepegawaian dan Diklat Daerah Kabupaten Takalar - Akhmad Akhmad (Journal of Government Insight, 2022)
This paper aims to determine the effectiveness of the filing system implementation at the Education and Training and Regional Personnel Board of Takalar Regency, in addition to knowing the factors that affect the effectiveness of the archive system implementation at the Education and Training and Regional Personnel Agency of Takalar Regency. This study uses a descriptive type of research. The implementation of the archive system at the Office of the Regional Personnel and Education and Training Agency of Takalar Regency has been running effectively. This is supported by the application of a modern archive system and also supported by the quality of Human Resources who are experts in the field of archives and the availability of facilities and infrastructure in the field of archives